2007
DOI: 10.2105/ajph.2005.076661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal and Provider Characteristics on Up-to-Date Immunization Status of Children Aged 19 to 35 Months

Abstract: We found that children of less educated mothers and children in Hispanic and non-Hispanic Black families with low income-to-poverty ratios were more likely to have completed the 4:3:1:3 series. Although the reasons for these results need further exploration in other data sets, possible factors are Hispanics' positive cultural attitudes regarding the needs and importance of young children and provision of information on immunizations to low-income minority mothers who access government-subsidized health care pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
5
37
2
5
Order By: Relevance
“…White participants had 14%-21% lower coverage in comparison with Black and Hispanic participants. These findings are similar to characteristics of unvaccinated children found in US studies, with unvaccinated children more likely to be White, male, or have a college-educated parent [29][30][31][32].…”
Section: Discussionsupporting
confidence: 84%
“…White participants had 14%-21% lower coverage in comparison with Black and Hispanic participants. These findings are similar to characteristics of unvaccinated children found in US studies, with unvaccinated children more likely to be White, male, or have a college-educated parent [29][30][31][32].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies that examined factors associated with vaccine uptake found both positive and negative associations with education level and income 21, 22, 23, 24. In this study, we found that many reasons for unwillingness to receive vaccine were similar in higher and lower education groups; however, the qualitative responses of some participants may suggest that while those with lower education levels have specific beliefs or reasons for not wanting vaccine, those with higher education levels have non‐specific preferences not to get vaccinated.…”
Section: Discussionmentioning
confidence: 93%
“…35 In the available administrative data, the best approximation of English proficiency was language spoken at home and interpreter need. Four risk factors with supporting evidence were not available in the database: low parent educational attainment, 12,19,23 single-parent household, 12,19,24,25 adolescent exposure to intimate partner violence, 27 and discontinuous insurance coverage. [29][30][31] Risk factors involving parents were based on biologic parents, regardless of whether they lived in the child's household.…”
Section: Identification Of Social Complexity Risk Factorsmentioning
confidence: 99%
“…We could not identify all social complexity risk factors associated with use patterns in prior studies. 12,19,[23][24][25]27,[29][30][31] To be included in the initial cohort, children had to have an identifiable biologic parent and at least 1 month of Medicaid coverage during the study period, resulting in the exclusion of 13% of otherwise eligible children. In assessing the child's exposure to social risk in the context of their family and environment, we were limited to biologic parents.…”
mentioning
confidence: 99%